THE ‘BRIEF NARRATIVE’ STYLE OF CLORINDA MATTO: FROM ROMANTIC LEGEND AND TRADITION TO MODERNISM - Velasquez Castro, Marcel (2012)
Clorinda Matto de Turner (1852-1909) for many years practiced «brief narrative» style in three different ways traditions, legends and story-telling. Some texts of the last group are really tales. This investigation has permitted the identification of fifty-nine traditions, ten legends and nine stories, a textual corpus that may be identified scattered among books and periodical publications of the nineteenth century. In this article the traditions of Cuzco are studied from the stand-point of three variable principles: first, social aestheticism of a contemporary reality (that of the ‘present’ —the time of writing—) with a view to building up a vision of the past; second, the global significance of the traditions as a political project; and third, the different positions adopted by the writer. The romantic legends are analysed from the following aspects: the marvel lous and mythical dimension of the Andean world, the melodramatic codes and sexual commerce between different races and the tensions between two different cultures (an Andean world is represented but the reflexions it generates are western). Finally the stories that the Cuzco authoress gives us, which are in fact an important link in modern Peruvian narrative, will be studied, once again, from three points of view: the presentation of the urban experience of her time, new narrative techniques, and the desire to conciliate the new values of modernization and those of a traditional religious society.